Enhancing Learning Abilities through Problem-Based Learning: A Meta-Analysis at Sanggar Bimbingan Hulu Kelang - Azizah, Siti Nur; Zahry, Ariel Alvi; Mumfaza, Risqia; Amala, Rizkika Ahsanu; Roisah, Roisah; Agustin, Valya Hanindita (Jurnal Ilmiah Kampus Mengajar, 2023)
Traditional learning methods in schools often involve passive activities such as listening, completing assignments, and focusing solely on textbooks. This lack of interaction between teachers and students, or among students themselves, can lead to ineffective learning and lower student outcomes. This research aims to analyze the effectiveness of the Problem-Based Learning (PBL) model in enhancing learning abilities at Sanggar Bimbingan Hulu Kelang. The study employs a meta-analysis method, with data collected through field observations and document reviews. The data was then analyzed both descriptively and qualitatively. The results indicate that the PBL model significantly improved students’ learning abilities, with an increase from a low of 8.9 percent to an average of 83.3 percent. The PBL model has proven effective in enhancing social studies learning outcomes for elementary school students. The findings of this research can assist teachers in selecting an appropriate learning model to improve student learning outcomes.